Nanotechnology in dentistry - Melanie Sadono Djamil (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Technology has continuously improved along with the complexity of devices. Nowadays, it is widely accepted that micro-technology, which is defined as a further reduction in the size of interconnections and components, is achieved by a conventional “top-down” method. We have now moved to a new concept and approach for fabrication from small to bigger building-block elements, which is called nanotechnology. Nanotechnology is the fabrication technology of tiny parts that is achieved by a “bottom-up” method. Nanotechnology has been developed in many areas of life sciences, such as in dentistry. This presentation provides some examples that illustrate the progress in technological growth, especially in the nanoscale. In the developments of nanotechnology, we are also concerned in many ways about its ethics and the laws of physics. The expansion in nanotechnology shows that much multidisciplinary research is being done in the nanoscale area. In dentistry, one of the examples is research in dental materials such as nanoleakage types in the use of various adhesives with resin composition. Nanodiagnostics are nanotechnology in applied molecular diagnostics. All these fields have applications in diagnostics and in point-of-care hand-held devices.